PENGARUH KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP MOTIVASI SERTA DAMPAKNYA PADA KINERJA KARYAWAN PT. BANK SYARIAH MANDIRI CABANG BANDA ACEH - Afriadie Kurniawan; Mukhlis Yunus; M. Shabri Abdul Majid (Jurnal Manajemen Inovasi, 2017)
ABSTRACTThis study aims to determine the effect of compensation and career development on employee motivation and its impact on the performance of employees of PT. Bank Syariah Mandiri branch of Banda Aceh. Samples were all employees who worked at PT. Bank Syariah Mandiri BRANCH BANDA ACEH totaling 128 employees. The analytical method used is multiple linear regression. The results showed that compensation and career development have a significant effect both simultaneously and partially on employee motivation and performance of employees of PT. Bank Syariah Mandiri BRANCH BANDA ACEH. Employee motivation acts as a partial mediator between the effect of compensation and career development on employee performance PT. Bank Syariah Mandiri branch of Banda Aceh. The implications of this research, PT. Bank Syariah Mandiri branch Banda Aceh need to improve the systems and mechanisms of good compensation to employees as well as creating a career development professional to be able to have an impact on employee motivation and performance of employees of PT. Bank Syariah Mandiri BRANCH BANDA ACEH.Keywords : Compensation, Career Development, Employee Performance.